Preparation and characterization of the heat-resistant UV curable waterborne polyurethane coating modified by bisphenol A (eXPRESS Polymer Letters, 2010)
In this study, the modified ultraviolet (UV) curable waterborne polyurethane was obtained from isophorone diisocyanate (IPDI), polyethylene glycol (PEG, MW=600), α,α-dimethylol propionic acid (DMPA), hydroxyethyl acrylate (HEA) and bisphenol A. The rigid moiety was introduced into the main chain of polyurethane to improve its heat-resistance. The copolymer structure was confirmed by Fourier transform infrared spectroscopy (FT-IR). Thermal property and UV curable behavior of the coatings were investigated. The glass transition temperature (Tg) of the modified film was determined by differential scanning calorimetry (DSC). Thermal gravimetric analysis (TGA) was employed to investigate the thermal stability of the modified film. The results show that the average particle diameters increased from 69.25 to 95.12 µm as the content of bisphenol A increased from 0.00 to 9.25%. The optimum bisphenol A dosage was 7.23% (wt%), the Tg of the modified film increased by 7.07°C and 5% weight-loss temperature (233°C) increased by 14°C. The optimum irradiation time was 10–20 minutes after the coatings being painted on an armor plate at room temperature and initiator dosage was 5% (wt%) of the latex.